(3JMaI GdCTQGa HeYQaI GdCWQGas - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s ((3YeQ Hf CMeO Hf eMeO GHf ESQGFjd GdLQgei GdMfai s)
(3ChdgG (B:s
(3ef (B: (3YGeQ Hf SYO Yf CHj gQjQI s
(3BNQgG (B:s
(3Edi (B: (3eYeQ Hf QGTO Yf GdRgQi Yf YQhI Yf YGFTI s
(3ajg ef GdLRA (B60 (3Edi GdLRA (B73 (3ef JLRFI GdCUds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B241 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B65 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: ( (3bGHdg GdbGSe GdHQRGdi Ydi fSNI GdeUfa(B)s
Keywords: (3GdMOjK h GdeUWdMs